THE ROLE OF THE MEDAN CITY GOVERNMENT IN HANDLING SOCIAL CONFLICT IN MEDAN BELAWAN: Analysis Of Law Number 7 Of 2012 And Siyasah Dusturiyah - Widya Indah Pratiwi; Zulkifli Nas (STIT DARUL ULUM KOTABARU, 2026)
Social conflict in Medan Belawan is a fairly complex problem triggered by several main factors, namely economic factors, education, and family conditions (broken homes). In addition, there are also factors of ego and prestige between groups or regions that often trigger fights between groups. Conflicts usually start from small things such as taunts, shooting firecrackers, or the use of weapons such as SOS towards certain alleys. In this conflict, the Medan City government has a role in resolving conflicts in its region as specified in Law Number 7 of 2012 concerning the Handling of Social Conflicts providing a legal framework for resolution through three stages including: prevention, termination, and post-conflict recovery. This study aims to analyze the role of the Medan City government in handling social conflicts in Medan Belawan based on Law Number 7 of 2012 and assess the role of the Medan City government in handling social conflicts in Medan Belawan from a siyasah industrial perspective. The method used is empirical or non-doctrinal legal research. This research approach is based on legislation (statute approach), a case study in Belawan, and siyasah dusturiyah (legal system) to assess qonun (law), institutions, citizen rights, and government rights. The results of the study indicate that the local government has undertaken various efforts, such as building cooperation with religious leaders, holding deliberations at the village level, establishing a Social Conflict Resolution Task Force, and mapping conflict-prone areas. Efforts to achieve reconciliation through mediation and peace agreements between conflicting parties are also underway. From the siyasah dusturiyah perspective, the government's role in conflict management is a manifestation of the exercise of executive power, tasked with upholding justice, resolving disputes, and maintaining public order. However, its implementation still faces various obstacles, necessitating more comprehensive recovery efforts.